1999
DOI: 10.1152/jappl.1999.87.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on fat cell size and hormone-sensitive lipase activity

Abstract: This study was designed to examine the relationship between diet-induced insulin resistance/hyperinsulinemia, fat cell hypertrophy, and hormone-sensitive lipase (HSL) to elucidate whether an attenuated HSL activity leads to obesity. Female Fischer 344 rats were fed either a low-fat, complex-carbohydrate diet or a high-fat, refined-sugar (HFS) diet for 2 wk, 2 mo, or 6 mo. Adipose tissue morphology and HSL activity as well as plasma free fatty acid and glycerol levels were determined at these times. No differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 56 publications
7
52
1
1
Order By: Relevance
“…26,27) Hypertrophy of the adipocytes due to obesity decreases the release of adiponectin into the blood, and the release of free fatty acids is inversely increased as a result of the activation of hormone-sensitive lipase. 28) In the present study, there was no difference in the serum adiponectin concentration between the groups when the animals were sacrificed, but the serum free fatty acid concentration was significantly lower in the RCA diet group than in the WCS diet group. This is particularly interesting because there is accumulated evidence that the increased availability of free fatty acids in the muscle and liver 29,30) is associated with the reduced ability of insulin to stimulate the utilization and storage of glucose.…”
Section: Discussioncontrasting
confidence: 49%
“…26,27) Hypertrophy of the adipocytes due to obesity decreases the release of adiponectin into the blood, and the release of free fatty acids is inversely increased as a result of the activation of hormone-sensitive lipase. 28) In the present study, there was no difference in the serum adiponectin concentration between the groups when the animals were sacrificed, but the serum free fatty acid concentration was significantly lower in the RCA diet group than in the WCS diet group. This is particularly interesting because there is accumulated evidence that the increased availability of free fatty acids in the muscle and liver 29,30) is associated with the reduced ability of insulin to stimulate the utilization and storage of glucose.…”
Section: Discussioncontrasting
confidence: 49%
“…When controlled for adipocyte cell size, the amount of HSL protein and HSL mRNA levels in subcutaneous adipocytes show a strong correlation with maximum lipolytic activity (51). A positive relationship between fat cell size and HSL expression was also seen with high fat feeding in rats, where fat feeding was associated with an increase in adipocyte cell size and an increase in both basal and stimulated HSL activity (52). In contrast, following several days of food deprivation in the rat, there is a ‫ف‬ 2-fold increase in HSL activity, immunoreactive protein, and mRNA levels in adipose tissue that is not observed with short term fasting and is associated with a reduction in fat cell size (53).…”
Section: Adipose Tissuementioning
confidence: 69%
“…Early events in Zucker fatty rat R Liu et al activity of hormone-sensitive lipase (HSL) in adipose cells are needed 30 to clarify the mechanism by which plasma FFA increases in the early stage of obesity. Contrary to the classical mechanism of FFA-induced insulin resistance as proposed by Randle et al 12 in which FFA exerts their effect through initial inhibition of pyruvate dehydrogenase, Roden et al found that elevation in plasma FFA concentration caused insulin resistance by inhibition of glucose transport and=or its phosphorylation with a subsequent reduction of glucose oxidation and muscle glycogen synthesis.…”
Section: Discussionmentioning
confidence: 99%